A practical macro-mechanical model for the bend capacity of fibre-reinforced polymer bars. Issue 10 (14th October 2021) - Imjai, Thanongsak; Guadagnini, Maurizio; Pilakoutas, Kypros; Garcia, Reyes; Sukontasukkul, Piti; Limkatanyu, Suchart
Abstract : Bent fibre-reinforced polymer (FRP) bars embedded in reinforced concrete elements resist lower forces than straight counterparts due to strength losses at the bend, and such losses are difficult to calculate. This paper reports on an investigation into the effect of section geometry and bond, which led to a new macro-mechanical model to calculate the bend capacity of FRP bars. The proposed model uses the Tsai–Hill failure criterion and accounts for factors known to influence the bend capacity of bars. A section factor, ignored in existing models, also accounts for the strength degradation due to the change in geometry at the bent portion of the bar. The model was calibrated using a set of 80 tests found in the literature and tests performed by the authors. The results indicated that, compared with existing equations, the proposed model predicts the bend strength of bars more accurately, with an average prediction to experiment ratio of 1·0 and a standard deviation of 0·25. Following validation and verification, appropriate values for the model parameters are recommended for design. The proposed model can lead to more economical design, by up to 15%.